Zakat Investment In Trade Field, The Law And The Rulling Foundation In The Islamic Jurisprudence - Santoso, Agus (2012)
The phenomenon of many rich people who do not want to pay the zakat is a major cause of the minimum number of zakat that can be collected and distributed to the needed. when it is compared with the number of homeless and from people, relying on that fact, some institutions of zakat take the initiative to invest zakat on those varions, of which the trade, which have the goal to develop zakat multiply to solve problems in society and to meet the needs of people homeless and in need of assistance. Considering the importance of this issue, the researcher wanted to present it in the study because this phenomenon has spread especially in our society. In that study there are two formulation of the problem, namely: What is the rulling of zakat investment in trade according to Islamic jurisprudence? What is the rulling foundation of the zakat investment in the field of trade? Researchers used this type of research : a qualitative study that is looking for a good variety of data written or seen or heard, this study is also a kind of library research, the research data and information obtained from major books related to this search. Researchers used two methods: the first - An inductive approach is to search for specific data related to this issue from a variety of primary sources to acquire essential knowledge, and the second - The analytical methods, the researcher is seeking information relating to zakat investment in trade to clarify a real issue before deciding on a more correct opinion in this case. The results of this study is that zakat investment in trade, has three conditions: First - investment by the recipient of charity zakat, scholars determined that the law is allowed. Second - The investment by the zakat payer, it is not allowed because they do not manifest the immediate payment of zakat. Third - Zakat investment by the president or a substitute, contemporary scholars have diferent opinions about this, and the most correct opinion is the law allow, it as long as it is in accordance with the given law, because there are some postulate suport it: in terms of texts (Al Hadith), from the political side of Islam, from the point of view of the goodness and the realization of the Islamic law's objectives, and from the side of qiyas. The most important zakat investment rulling foundation is that the charity is run after the investment met the urgent needs of the poor in the form of clothing, food, medicine and others.